ANALISIS STRATEGI INFLUENCER MARKETING PADA INSTAGRAM STUDIO DAPUR TAHUN 2024 - Yudhistira Akhmad Kurniawan; Widya Sastika (POLITEKNIK LP3I JAKARTA, 2024)
Business competition has significantly increased over time as various companies introduce innovative flagship products. Consumers are more likely to choose well-known brands when selecting products. Therefore, companies must find effective marketing strategies to ensure that consumers recognize the products or services offered. One factor that can influence a company's or enterprise's recognition is improving brand awareness. To increase brand awareness, one of the most appropriate strategies is using influencers as part of promotions, or influencer marketing. Influencer marketing involves promoting products through influencers to their followers. The purpose of this research is to understand the stages and implementation of influencer marketing at Studio Dapur. The method used in this research is descriptive qualitative, consisting of participatory observation, interviews, documentation, and triangulation. The results of this study conclude that the implementation of the influencer marketing strategy on Studio Dapur's Instagram has yielded positive results, particularly in terms of engagement rate, with an average achievement of 1-5% from the four influencers used. These results indicate strong performance and have a direct impact on increasing brand awareness.